1978
DOI: 10.1128/iai.22.2.508-515.1978
|View full text |Cite
|
Sign up to set email alerts
|

Experimental urinary tract infection with Pseudomonas aeruginosa in mice

Abstract: Urinary tract infection with Pseudomonas aeruginosa was induced in mice by transurethral inoculation of the organism into the bladder, followed by urethral obstruction for 6 h. The infection was mostly localized in the urinary organs. P. aeruginosa P 9 was selected as the challenge organism from 10 laboratory strains of P. aeruginosa. After the inoculation of 107 colony-forming units of P. aerugi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Agglutination test. Serum agglutinating antibody against K. pneumoniae 27 was examined by the microtiter method as described previously (14).…”
Section: Methodsmentioning
confidence: 99%
“…Agglutination test. Serum agglutinating antibody against K. pneumoniae 27 was examined by the microtiter method as described previously (14).…”
Section: Methodsmentioning
confidence: 99%
“…Marked ulceration of the bladder after pseudomonas infection has been (Hematoxylin and eosin stain; xl,OOO, approximately) described in rats with prior injury of the bladder wall (14). Other studies of the histological changes in the bladder have not noted ulceration with pseudomonas (13) or Escherichia coli (3,15). In preliminary studies, we have observed ulceration of bladder in mice after injection of E. coli (unpublished observations).…”
mentioning
confidence: 97%
“…Experimental studies of the urinary tract have dealt mainly with the kidney infections associated with pseudomonas infection (4,6,7,13). There have been few clinical or experimental studies of pseudomonas infection in the lower urinary tract.…”
mentioning
confidence: 99%
“…The low susceptibility to UTI in most laboratory animals has been an obstacle in the search for useful animal models. To cause the UTI in experimental animals by interrupting the host defense mechanisms, various researchers applied different treatments to increase the susceptibility by obstructions of the ureter (4) or urethra (17,24), kidney or bladder massage (3,11), implantation of a glass bead (25), injection of acid (6), the scars of antecedent bacterial infection (7,21), or glucose-induced diuresis (15).…”
mentioning
confidence: 99%